An investigation of non-linear optimization methods on composite structures under vibration and buckling loads - Akbulutla, Mustafa; Sarac, Abdulhamit; Ertaş, Ahmet Hanifi (Techno-Press, 2020)
In order to evaluate the performance of three heuristic optimization algorithms, namely, simulated annealing (SA), genetic algorithm (GA) and particle swarm optimization (PSO) for optimal stacking sequence of laminated composite plates with respect to critical buckling load and non-dimensional natural frequencies, a multi-objective optimization procedure is developed using the weighted summation method. Classical lamination theory and first order shear deformation theory are employed for critical buckling load and natural frequency computations respectively. The analytical critical buckling load and finite element calculation schemes for natural frequencies are validated through the results obtained from literature. The comparative study takes into consideration solution and computational time parameters of the three algorithms in the statistical evaluation scheme. The results indicate that particle swarm optimization (PSO) considerably outperforms the remaining two methods for the special problem considered in the study.
Keywords: Benchmarking; Heuristic optimization algorithms; structural optimization; laminated composites; buckling load; fundamental frequencies